Fair Value Accounting and Measurement through FASB's Developments - Carmen Giorgiana Bonaci; Jiří Strouhal; Dumitru Matis (European Financial and Accounting Journal, 2009)
Our research follows the path of fair value as a term and concept, as well as its disclosure, measurement and recognition back from 1953 until our days, and analyzes the regulations issued by United States Accounting Standard setters, through the point of view of the historical events, which led to their appearance. Our study brings its' contribution to complementing growing literature on the value relevance of fair value, but focuses on the assessment of fair value as a financial reporting standard for financial instruments. The objective of the paper is to link the regulations with the historical events, which have guided them to their current shape and meaning. In doing so, we identified several key issues, which need to be analyzed, and through which we draw our conclusions after a closer analysis of SFAS's foresights. In financial reporting, United States and International Accounting Standard setters have issued several disclosures, measurement and recognition standards for financial instruments. We conclude our study noticing how all indications are that both standard setters mandate recognition of financial instruments at fair value, despite all fingers currently being pointed toward fair value as a “scape goat” for the recent events. The relevance of the study is emphasized when looking through the lens of the current financial crisis, derivative financial instruments being a central element. With Churchill's words and believe in our thoughts, “the deeper we can look into the past, the farther we'll see into the future” we plead for fair value assessment by underlying its advantages, while being aware of its limitations.
Keywords: M41; 650; Fair value; Hierarchy Level; Reliability; Relevance; Estimates; Financial crisis